Century-scale changes in phytoplankton phenology in the Gulf of Maine - Record, Nicholas R. (PeerJ, 2019)
The phenology of major seasonal events is an important indicator of climate. We analyzed multiple datasets of in situ chlorophyll measurements from the Gulf of Maine dating back to the early 20th century in order to detect climate-scale changes in phenology. The seasonal cycle was consistently characterized by a two-bloom pattern, with spring and autumn blooms. The timing of both spring and autumn blooms has shifted later in the year at rates ranging from ∼1 to 9 days per decade since 1960, depending on the phenology metric, and trends only emerged at time scales of >40 years. Bloom phenology had only weak correlations with major climate indices. There were stronger associations between bloom timing and physical and chemical variables. Autumn bloom initiation correlated strongly with surface temperature and salinity, and spring bloom with nutrients. A later spring bloom also correlated with an increased cohort of Calanus finmarchicus, suggesting broader ecosystem implications of phytoplankton phenology.